Effect of liraglutide treatment on body mass index and weight parameters in children and adolescents with type 2 diabetes: Post hoc analysis of the ellipse trial. - Bensignor, Megan O.; Bomberg, Eric M.; Bramante, Carolyn T.; Divyalasya, T. V. S.; Hale, Paula M.; Ramesh, Chethana K.; Rudser, Kyle D.; Kelly, Aaron S. (Pediatric Obesity, 2021)
Summary: Background: Weight loss in children and adolescents with type 2 diabetes (T2D) is associated with improved glycaemic control. Objectives: To assess the effects of liraglutide vs placebo on body mass index (BMI) and weight parameters in children and adolescents with T2D using data from the ellipse trial (NCT01541215). Methods: The ellipse trial randomized participants (10‐<17 years old, BMI >85th percentile, T2D, glycated haemoglobin [HbA1c] 7.0%‐11.0% [if diet‐ and exercise‐treated] or 6.5% to 11.0% [if treated with metformin, basal insulin or both]) to liraglutide or placebo. This post‐hoc analysis evaluated changes from baseline to weeks 26 and 52 in absolute BMI, percent change in BMI and other weight‐related parameters. Changes were assessed by liraglutide overall (all doses) and liraglutide by dose (0.6, 1.2 and 1.8 mg/day) vs placebo using a pattern mixture model of observed data, with missing observations imputed from each treatment group. Results: In total, 134 participants were included. There were statistically significant differences between groups in certain parameters, including absolute BMI (estimated treatment difference [ETD] –0.89 kg/m2; 95% confidence interval [CI] –1.71,–0.06) and percent change in BMI (ETD –2.73%; 95% CI –5.15,–0.30) at week 52, but none at week 26. Dose‐dependent effects were not observed for liraglutide vs placebo for all BMI/weight parameters. Conclusions: Compared with placebo, liraglutide was associated with statistically significant reductions in BMI/weight parameters at week 52, but not week 26, in children and adolescents with T2D.